Analisis Perbandingan Akad pada Platform Shopee dan Tokopedia dalam Sistem Penjualan Dropshipping - Sari, Novita; Suud Maadi, Alan (IAIN Langsa, 2024)
Ideally, the dropshipping sales system implemented on e-commerce platforms such as Shopee and Tokopedia should operate with clear transparency, avoid elements of gharar, and align with the principles of Islamic economic law. However, in practice, the application of contracts on both platforms still shows differences that affect the efficiency and effectiveness of transactions. This study aims to analyze the comparison of contracts applied on the Shopee and Tokopedia platforms in the dropshipping sales system and assess how well they align with the principles of Islamic law. This article is categorized as normative legal research based on qualitative methods, using a comparative study approach explained through descriptive analysis. The research findings conclude that the contracts applied on Shopee and Tokopedia, namely salam and wakalah contracts, meet the requirements of sales contracts in Islamic law while ensuring transparency, price certainty, and delivery time. Shopee shows an advantage in faster delivery times due to its advance payment system, while Tokopedia excels in effectiveness due to policies and features that support buyer security and trust, such as buyer protection and shipment tracking.